2003
DOI: 10.1001/archinte.163.19.2368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lifestyle on Hemostasis, Fibrinolysis, and Platelet Reactivity

Abstract: The pathophysiology of atherothrombosis in cardiovascular disease is complex and multifactorial. No doubt, lifestyle habits such as exercise, smoking, diet, and alcohol consumption may have significant influence on cardiovascular disease. As the hemostatic system is assuming an increasingly prominent role in the pathogenesis and progression of atherovascular diseases, this review evaluates the effects of lifestyle habits (or lifestyle modifications) on blood coagulation, fibrinolysis, and platelet reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
166
2
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(175 citation statements)
references
References 282 publications
(246 reference statements)
1
166
2
6
Order By: Relevance
“…Some previous studies showed an inverse association between omega-3 PFA and plasma fibrinogen, although these findings have been inconsistent. 23 In our study, higher omega-3 PFA intake in Japanese in Japan did not independently explain lower fibrinogen levels in Japan. This may be because of a relatively small difference in omega-3 PFA intake across the samples from Japan and Hawaii, with fish intake relatively high at both sites.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Some previous studies showed an inverse association between omega-3 PFA and plasma fibrinogen, although these findings have been inconsistent. 23 In our study, higher omega-3 PFA intake in Japanese in Japan did not independently explain lower fibrinogen levels in Japan. This may be because of a relatively small difference in omega-3 PFA intake across the samples from Japan and Hawaii, with fish intake relatively high at both sites.…”
Section: Discussioncontrasting
confidence: 58%
“…To the best of our knowledge, there is no previous report on a relationship between sugar intake and plasma fibrinogen. 23 A recent study reported an association between high dietary glycemic load and elevated C-reactive protein. 25 Inflammation may result from recurrent postprandial hyperglycemia, hyperinsulinemia, and insulin resistance that may occur with long-term high dietary glycemic load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, however, we found a decrease in PAI-1 both in the lifestyle intervention group that continued metformin treatment and in the group that stopped metformin and combined lifestyle intervention with insulin treatment. Other studies have consistently reported significantly decreased PAI-1 levels following regular exercise and there is ample evidence that weight reduction reduces PAI-1 and tissue-type plasminogen activator antigen levels in non-diabetic subjects [47]. Still there is a risk that stopping metformin in groups L+I and I may have contributed to the differences between these groups and group L at the end of the study.…”
Section: Discussionmentioning
confidence: 89%
“…Benefits to the circulatory system include influences on the lipoprotein metabolism, inflammatory markers, endothelial function and insulin resistance. [39][40][41][42][43][44][45][46] Is physical activity important among those who lose weight? Our study showed that leisure time physical activity had protective effect on all-cause mortality, which is in line with numerous other studies.…”
Section: Discussionmentioning
confidence: 99%